Parental perception of mental health needs in young children. Issue 4 (15th October 2021) - McGinnis, Ellen W.; Copeland, William; Shanahan, Lilly; Egger, Helen L.
Abstract : Background: There is evidence of unmet psychiatric needs in children under 6. These young children are dependent on their parents to identify their mental health needs. This study tested child and parent associations with parent perception of young child mental health need. Method: Parents of 917 children (aged 2–6 years) completed a diagnostic interview about their child assessing depression, anxiety, ODD/CD, ADHD, and impairment. Parents were surveyed about their own depression, anxiety, and asked about their psychiatric impairment. Parents were also asked whether they perceived their child as having a mental health need. Results: Only 38.8% of children who met criteria for a diagnosis were perceived by their parents as having a need, similar to previously studied rates in school‐aged children. Perception of need was associated with higher levels of symptoms and impairment. Thresholds for at least half of parents perceiving their child as having a need were relatively high: 19 or more symptoms, or 4 or more impairments. There was evidence of specificity: children with depressive disorders were more likely to be perceived as in need compared with other disorders. In terms of parent factors, more parental depressive symptoms were associated with higher perception of child need when the child had a diagnosis. Parental psychological impairment was associated with higher perception of need when the child had no diagnosis. Conclusions: Most preschool children that meet criteria for a psychiatric disorder are not perceived as needing help by their parents, which is dependent on both child and parent factors.